Selection criteria for major events in sport. Guidelines and tips (Sport Dispute Resolution Centre of Canada (SDRCC), 2008)
Canadian athletes, coaches, officials and other members of the sport community are subject to a selection process in order to participate in the various sporting events at the different levels. The process by which they are selected can lead to disagreements and disputes. The Sport Dispute Resolution Centre of Canada .SDRCC. has published this brochure to assist members of the sport community to understand the basic principles of team selection and to build sound team selection policies that will reduce the risk of disputes. Although this text focuses on the selection of athletes at the national level, most of its content is equally applicable to the selection of the other members of a team such as coaches, officials, volunteers, etc. as well as to the selection of any team in competitive sport. The following sections are examples of major events to which many Canadian athletes aspire to participate, and some particularities about their applicable selection processes: Olympic, Paralympic, PanAmericanGames,Commonwealth and World University Games.